Sensitivity of clinician‐assessed efficacy outcome measurement instruments in trials of topical therapies for atopic dermatitis: a systematic review and meta‐analysis. (22nd November 2021) - Légaré, S.; Chagnon, M.; Palijan, A.; Kojok, K.; Bissonnette, R.
Abstract: The rising prevalence of atopic dermatitis (AD) in developing countries and its substantial socioeconomic impact have furthered research over the last two decades giving way to advances in its aetiopathogenesis and treatment. Topical therapies targeting newly identified AD signalling pathways are being developed. Numerous clinician‐assessed disease severity outcome measurement instruments (OMIs) are available to evaluate the efficacy of investigational treatments in proof‐of‐concept (POC) trials for AD. However, little is known about the comparative sensitivity of these efficacy OMIs. We performed a systematic review and meta‐analysis to compare the sensitivity of different OMIs in controlled trials of topical therapies for AD published between January 1, 2000 and April 7, 2020. Treatment effect size of OMIs reported at Week 4 was calculated with 95% Confidence Interval (CI). The sensitivity of OMIs was compared by pooling the standardized difference between means (Cohen's d and Cohen's h ) for any two OMI‐parameter combinations that were reported in ≥3 studies identified in our systematic review. Assessed parameters were difference between active and vehicle at Week 4 and change from baseline [ CFB ] and percentage change from baseline [ %CFB ] at Week 4. We identified a total of 15 studies with 3313 subjects examining 14 different OMIs were included in this quantitative meta‐analysis. Continuous OMIs had a significantly higher treatment effect size vs. dichotomous OMIs ( P = 0.006). Comparisons of Eczema Area and Severity Index (EASI), Investigator's Global Assessment (IGA), body surface area (BSA) and SCORing Atopic Dermatitis (SCORAD) for available parameters were performed and generally had a similar sensitivity, with BSA showing smaller overall effect size estimates. In conclusion, continuous OMIs used in topical clinical trials for AD had significantly higher treatment effect sizes when compared to dichotomous OMIs. Continuous OMIs could provide more power for POC trials with a small sample size in atopic dermatitis with topical therapies.